Determinants of Consumer Purchase Decisions with Price and Personal Factors as Control Variables - Abrori, Imam; Ariescy, Reiga Ritomiea (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
Research on the factors that influence consumer decisions to buy goods at Indomaret campus area, Jember. The purpose of this study is to analyze the effect of store layout and interior display on purchasing decisions. The number of samples used in this study was 50 people with purposive sampling and quota sampling techniques. The data collection method used in this study used a questionnaire. The analysis used includes data instrument test (validity test and reliability test), multiple linear regression analysis. From the results of data analysis, it can be seen that store layout has a positive effect on consumer decisions to make purchases at Indomaret. Meanwhile, the Interior display has no effect on consumer purchasing decisions at Indomaret. This shows that consumers do not pay much attention to the things contained in the interior display, such as store design according to the day of celebration, provision of baskets, and advertisements in the store. After entering the control variables, namely price variables, and personal factors, the test results both show that store layout and interior display have no effect on consumer decisions to make purchases at Indomaret.